PARP Inhibition Attenuates Histopathological Lesion in Ischemia/Reperfusion Renal Mouse Model after Cold Prolonged Ischemia. (11th November 2013) - del Moral, Raimundo M. G.; Gómez-Morales, Mercedes; Hernández-Cortés, Pedro; Aguilar, David; Caballero, Trinidad; Aneiros-Fernández, Jose; Caba-Molina, Mercedes; Rodríguez-Martínez, Mª Dolores; Peralta, Andreina; Galindo-Moreno, Pablo; Osuna, Antonio; Oliver, F. Javier; et al.
Abstract : We test the hypothesis that PARP inhibition can decrease acute tubular necrosis (ATN) and other renal lesions related to prolonged cold ischemia/reperfusion (IR) in kidneys preserved at 4°C in University of Wisconsin (UW) solution. Material and Methods . We used 30 male Parp1 +/+ wild-type and 15 male Parp1 0/0 knockout C57BL/6 mice. Fifteen of these wild-type mice were pretreated with 3, 4-dihydro-5-[4-(1-piperidinyl)butoxyl]-1(2H)-isoquinolinone (DPQ) at a concentration of 15 mg/kg body weight, used as PARP inhibitor. Subgroups of mice were established (A: IR 45 min/6 h; B: IR + 48 h in UW solution; and C: IR + 48 h in UW solution plus DPQ). We processed samples for morphological, immunohistochemical, ultrastructural, and western-blotting studies. Results . Prolonged cold ischemia time in UW solution increased PARP-1 expression and kidney injury. Preconditioning with PARP inhibitor DPQ plus DPQ supplementation in UW solution decreased PARP-1 nuclear expression in renal tubules and renal damage. Parp1 0/0 knockout mice were more resistant to IR-induced renal lesion. In conclusion, PARP inhibition attenuates ATN and other IR-related renal lesions in mouse kidneys under prolonged cold storage in UW solution. If confirmed, these data suggest that pharmacological manipulation of PARP activity may have salutary effects in cold-stored organs at transplantation.